Turcish publicism and is role society - Aбуовa A. Т.; Мaхсутовa A. (Journal of Oriental Studies, 2017)
The article is about Turkish publicistical style genres, types, role in society and important sides. Publicistic style is the most widely used and popular style. Publicistic style-political, cultural, sports, etc. in the framework of a functional language, serving a kind of public relations. Publicistic style is containedpolitical information in various newspapers, magazines, brochuresin Turkish society. There are issues specific to Turkish publicistic style: imagery and political clarity. These matters occur to formulate people’s consciousness, public opinion for social purpose.